(untitled) (El-Wahat Journal for Research and Studies, 2025)
Foreign Direct Investment Has A Major Role In The Development Of Developing Economies, And A Means Of Imposing Influence For Developed Countries. This Study Came To Shed Light On The Reality Of The Investment Climate In Algeria During The Period 1977-2019, By Clarifying The Ability Of The Investment Climate To Diagnose Its Most Important Features Through Some International Indicators, Which Lead Us To Extract The Strengths And Weaknesses Of This Climate., And Formulate A New Strategy A Scientific Approach To Attract Foreign Direct Investment Based On Improving The Investment Climate And Focusing On Political Reform And Good Governance. Keywords: Foreign Direct Investment, Investment Climate In Algeria, International Indicators Of Investment Climate.